Wunderlich's syndrome due to spontaneous rupture of large bilateral angiomyolipomas. Issue 1 (22nd December 2008) - Moratalla, M Ballesta
Abstract : Spontaneous renal haemorrhage, or Wunderlich's syndrome, is an unusual cause of acute abdomen. It is a rare disease, usually secondary to tumours, and is an emergency and life-threatening condition. CT scanning is highly recommended to achieve a definitive diagnosis and to determine the approach to follow, trying to use conservative surgery whenever possible, although our case was treated with nephrectomy. The case history is reported of spontaneous renal haemorrhage or Wünderlich syndrome secondary to bilateral giant renal angiomyolipomas in a 21-year-old patient with tuberous sclerosis.